C++ programmer's notebook : - Keogh, Jim (Prentice Hall PTR, 1998)
A tutorial/reference to C++++ uses graphics to illustrate key concepts and provides programmers with a clear picture of how to develop applications, providing accompanying illustrations for every included code examples.